J. Gelaževičius’ Collection of Books at the Scientific Library of the Vilnius State University - Stravinskas, Antanas (Knygotyra, 1976)
The present article deals with the collection of books and other publications given over to the Vilnius University Library by J. Gelaževičius, a student of the university in 1945–1950, an engineer of forestry, a teacher of botany at the Kaunas A. Kvedaras technical school of forestry, an Honoured Teacher of the Lithuanian S.S.R., on its 400th anniversary.The collection had 4784 items by September 24th 1974: 3533 books, 1194 periodicals, 14 manuscripts, 4 maps and 39 placards.The collection falls into three parts: A. Main literature (literature on botany, biology, zoology and forestry); B. Secondary literature (literature on geology, mineralogy, soil science and geography) and C. Other literature (books by the authors of marxism, linguistics and literature, pedagogics, etc.).The collection comprises books in Lithuanian, Russian, Polish, German, English, Czech and other languages.The collection is being enriched by older and latest publications on the natural sciences, forestry and some other branches of science.J. Gelaževičius gift is one of the largest and most valuable collections in possession of the Scientific Library of the Vilnius State University.